Complications after Cranioplasty: A Pictorial Narrative with Techniques to Manage and Avoid the Same - Raju, Dimble; Bhosle, Rajesh; Patel, Shamshuddin; Bhattacharyya, Asis Kumar; Aditya, Grandhi; Krishnan, Prasad (Indian Journal of Neurotrauma, 2023)
Background Cranioplasty following decompressive craniotomy is considered to be a “routine procedure” but several large series have documented a significant amount of both delayed and immediate complications and also a mortality rate of up to 3.6%.Materials and Methods We went through some of the salient complications (excluding seizures) needing resurgery following interval cranioplasty over the past 18 years at our institution in over 300 cases and analyzed the literature that mention these complications and their treatment.Results In addition to the commonly mentioned complications, we found some that had been rarely described or not mentioned hitherto in the literature which we have presented as a pictorial narrative. Based on our experience, we recommend some measures that may decrease the incidence or prevent the occurrence of the same.Conclusions Attention to small but basic surgical techniques will go a long way in preventing unwanted postoperative events.
Keywords: decompressive craniotomy; cranioplasty; complications; infection; bone flap resorption; flap mobility; epidural fluid collection; extradural hemorrhage; flap subsidence